The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/pros.20156
|View full text |Cite
|
Sign up to set email alerts
|

Association of free-prostate specific antigen subfractions and human glandular kallikrein 2 with volume of benign and malignant prostatic tissue

Abstract: The multi-chain fPSA-N subfractions of fPSA may be a valuable predictor of both benign prostate hyperplasia (BPH) and CaVol that is likely to be more useful in predicting tz volumes than CaVols. fPSA-I may provide information on cancer without being influenced by the presence of BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Increasing hK2 was significantly associated with cancer volume, presence of ECE, and high-grade PCa (12)(13)(14).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Increasing hK2 was significantly associated with cancer volume, presence of ECE, and high-grade PCa (12)(13)(14).…”
Section: Discussionmentioning
confidence: 95%
“…It is, however, unclear whether protein concentrations in tissue correlate with those in circulation; PSA and hK2 concentrations are up to 10 6 -fold higher in tissue than in blood (11 ). Nevertheless, recent studies have demonstrated that hK2 concentrations in serum are significantly associated with extracapsular extension (ECE) of PCa and with the volume of PCa in prostatectomy specimens (12)(13)(14). Although these studies have provided indications that serum hK2 may be a predictor of advanced PCa, definitive evidence is lacking.…”
mentioning
confidence: 99%
“…15,16 Similarly, free and complexed PSA (cPSA) have been shown to be differentially associated with benign and malignant prostate tissue. 13,14 We therefore hypothesize that %fPSA and hK2 add greater predictive value closer to diagnosis.In our previous paper, 9 we reported associations between cancer and biomarkers measured in blood taken from men aged 50 or less who participated in a cardiovascular prevention project (MPM) in Malm€ o, Sweden. The project enrolled participants (74% acceptance rate) during 1974 -1986 .…”
mentioning
confidence: 98%
“…Moreover, some investigators have reported that free PSA (fPSA) and percent-fPSA (%fPSA) outperform PSA as predictors of prostate enlargement without PCa. [7][8][9] Previous studies have consistently shown that increased adiposity, as determined by various anthropometric measures, such as body weight (BW), 10 body mass index (BMI) [10][11][12] and waist circumference, 10,11 is positively associated with transrectal ultrasound-and with magnetic resonance imaging-measured TPV.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several predictive models estimating clinical prostatic enlargement based on levels of PSA or PSA derivatives, [6][7][8][9][10][11][12][13] Jacobson et al 13 recently reported that age and weight can be incorporated into models based on serum PSA levels to achieve greater accuracy when estimating TPV. However, predictive models including anthropometric measurements have never been investigated in Asia.…”
Section: Introductionmentioning
confidence: 99%